SISTEMA FERROVIÁRIO PÓS-PRIVATIZAÇÃO E FLUIDEZ CORPORATIVA: O MOVIMENTO DE PRODUTOS AGRÍCOLAS NO TERRITÓRIO BRASILEIRO - Vencovsky, Vitor Pires; Castillo, Ricardo (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2007)
The organization of the Brazilian territory has been defined mainly by public and private policies directed to the production, movement and exportation of agricultural commodities produced in Cerrado region. The competitiveness of the Brazilian agribusiness becomes dependent of a logistic in which the railroad assumes a preponderant role. This article intends to analyze the policies of the current railroad system and agriculture production areas that have a strong consequence to the corporative use of the Brazilian territory.